Responsivity to light in familial hemiplegic migraine type 1 mutant mice reveals frequency‐dependent enhancement of visual network excitability. (26th November 2020) - Perenboom, Matthijs J. L.; Schenke, Maarten; Ferrari, Michel D.; Terwindt, Gisela M.; van den Maagdenberg, Arn M. J. M.; Tolner, Else A.
Abstract: Migraine patients often report (inter)ictal hypersensitivity to light, but the underlying mechanisms remain an enigma. Both hypo‐ and hyperresponsivity of the visual network have been reported, which may reflect either intra‐individual dynamics of the network or large inter‐individual variation in the measurement of human visual evoked potential data. Therefore, we studied visual system responsivity in freely behaving mice using combined epidural electroencephalography and intracortical multi‐unit activity to reduce variation in recordings and gain insight into visual cortex dynamics. For better clinical translation, we investigated transgenic mice that carry the human pathogenic R192Q missense mutation in the α1A subunit of voltage‐gated CaV 2.1 Ca 2+ channels leading to enhanced neurotransmission and familial hemiplegic migraine type 1 in patients. Visual evoked potentials were studied in response to visual stimulation paradigms with flashes of light. Following intensity‐dependent visual stimulation, FHM1 mutant mice displayed faster visual evoked potential responses, with lower initial amplitude, followed by less pronounced neuronal suppression compared to wild‐type mice. Similar to what was reported for migraine patients, frequency‐dependent stimulation in mutant mice revealed enhanced photic drive in the EEG beta‐gamma band. The frequency‐dependent increases in visual network responses in mutant mice may reflect the context‐dependent enhancement of visual cortex excitability, which could contribute to our understanding of sensory hypersensitivity in migraine. Abstract : Migraine patients often report hypersensitivity to light, but the underlying network mechanisms are unclear. We here studied visual network responsivity relevant to migraine by simultaneous recording of EEG and multi‐unit activity during visual stimulation paradigms with flashing light in freely behaving wild‐type and familial hemiplegic migraine type 1 (FHM1) R192Q mutant mice. Mutant mice showed intensity‐ and frequency‐dependent changes in visual evoked potentials that indicate context‐dependent visual network hyperexcitability relevant to migraine.